Catholic Pastoral and Prophetic Responses to a Secularizing Landscape - Sullivan, John (Verbum Vitae, 2024)
The purpose of this article is to offer a retrieval of some major themes in the writings of Romano Guardini and Ivan Illich, two twentieth century Catholic priests who responded to secularization in ways that could be described as both pastoral and prophetic. Guardini tended towards a more pastoral emphasis, while Illich’s stance was more prophetic. Guardini exemplified a Catholic way to bridge the gap often experienced between faith, life and culture. Illich demonstrated how a Catholic can address their culture in a way that is both challenging and fertile and does so in penetrating observations about contemporary secular professions and preoccupations. The article has three parts. In part one, I sketch a range of responses to Christianity that have emerged in an increasingly secular culture, as well as the types of response that Christians have made to such a culture. In parts two and three a representative sample of the writings of Guardini and Illich is drawn on and analysed, together with a range of secondary literature on Guardini and Illich, in order to explain the nature and the role of four key themes (in each case) within their overall outlook. For Guardini, in part two, these are Catholic worldview, liturgy, providence and cultural critique. For Illich, in part three, I examine his notion of the mission of the Church, his treatment of schooling, his understanding that modernity is a perversion of Christianity, and his advocacy of friendship as a healing and liberating mode of engaging the world